Ultrastructural and Phylogenetic Description of Kudoa orbicularis n. sp. (Myxosporea: Multivalvulida): A Parasite Infecting the Muscle of the Fish Chaetobranchopsis orbicularis (Teleostei: Cichlidae) in the Amazon Region. (29th June 2015) - Azevedo, Carlos; Rocha, Sónia; Matos, Edilson; Oliveira, Elsa; Matos, Patrícia; Al‐Quraishy, Saleh; Casal, Graça
Abstract: A new myxosporean species is described from the muscle of the Amazonian freshwater fish Chaetobranchopsis orbicularis (Teleostei, Cichlidae), with basis on morphometric, ultrastructural and molecular data. Numerous myxospores were observed within pseudocysts located on the hosts' dorsal and ventral muscles, near the neural spines and neural canal (spinal cord). Mature myxospores quadrangular with rounded ends in apical view, measuring 4.3 (3.6–5.0) μm in length and 5.1 (4.2–5.8) μm in width. The myxospores wall is formed by four symmetric valves. Within, four pyriform polar capsules, 2.1 (1.7–2.6) μm long and 1.3 (0.9–1.7) μm wide, located two by two in opposite sides of the myxospores longitudinal axis, each containing a polar filament forming 2–3 coils. Molecular analysis of the SSU rRNA gene by maximum likelihood, neighbor‐joining and maximum parsimony confirms the parasite as a new member of the genus Kudoa, herein named Kudoa orbicularis n. sp., the second species of its genus reported from the South American freshwater fauna, and the fourth species worldwide known to occur in the freshwater environment. Furthermore, its sequence of the SSU rRNA gene constitutes the first entry of a freshwater Kudoa species in GenBank.